2018
DOI: 10.1016/j.bpobgyn.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Host control of human papillomavirus infection and disease

Abstract: Most human papillomaviruses cause inapparent infections, subtly affecting epithelial homeostasis, to ensure genome persistence in the epithelial basal layer. As with conspicuous papillomas, these self-limiting lesions shed viral particles to ensure population level maintenance and depend on a balance between viral gene expression, immune cell stimulation and immune surveillance for persistence. The complex immune evasion strategies, characteristic of high-risk HPV types, also allow the deregulated viral gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 55 publications
(57 reference statements)
1
92
0
4
Order By: Relevance
“…Unlike the humoral immune response against HPV that prevents infection by the virus, the responsible for the clearance of HPV infections is the cell-mediated immune response [36,37]. In this sense, T-cell homing and T-cell infiltration at the site of infection is related with the immune control and clearance of HPV infections [38]. However, there are times when the immune system is not able to control the progression of HPV infections or is unable to prevent recurrences in patients who have already been treated.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the humoral immune response against HPV that prevents infection by the virus, the responsible for the clearance of HPV infections is the cell-mediated immune response [36,37]. In this sense, T-cell homing and T-cell infiltration at the site of infection is related with the immune control and clearance of HPV infections [38]. However, there are times when the immune system is not able to control the progression of HPV infections or is unable to prevent recurrences in patients who have already been treated.…”
Section: Discussionmentioning
confidence: 99%
“…HPVs enter the cutaneous epithelium via the basal layer as a result of microtraumas and the viral life cycle is tightly linked to the differentiation program of the stratified squamous epithelium [7]. Many studies have demonstrated that α-HR HPVs deregulate proliferation and differentiation of infected cells via the expression of E6 and E7 oncoproteins, which are capable of interacting with several cellular proteins, including p53 and retinoblastoma (pRb) tumor suppressors respectively [6, 8-10].…”
Section: Structure and Classification Of Human Papillomavirusmentioning
confidence: 99%
“…Interestingly, the prevalence of specific cutaneous HPVs varies across diseases: α-4 HPVs 2, 27 and 57, γ-1 HPV-4 and µ-1 HPV-1 are the most prevalent types in common warts [17], α-8 HPV-7 is frequently detected in common warts of individuals working in humid and cold environments (e.g., butchers) [45], γ-1 HPV-4 and µ-1 HPV-1 predominate in plantar warts, and α-2 HPVs 3 and 10 are the most commonly detected in flat warts [7]. However, the etiological role of β-HPVs in cutaneous malignancies has proven difficult to delineate not only due to the high heterogeneity of this group of viruses but also because these infections are ubiquitously disseminated throughout the healthy skin, oral cavity, nasal mucosa and anogenital region, hindering the definition of infections that may be clinically relevant [29, 34, 36, 46, 47].…”
Section: Epidemiology Of Beta Hpv Associated Diseasesmentioning
confidence: 99%
“…The E6 and E7 proteins of oncogenic types of HPV stimulate cell proliferation by interacting directly, in addition to several other cellular proteins, with p53 and pRB proteins, respectively, both master regulators of the cell cycle [1]. The consequence is expansion of the life span of infected cells favoring the accumulation of mitotic defects, genomic instability and finally neoplasia development.…”
Section: Introductionmentioning
confidence: 99%
“…While E1 and E2 proteins play crucial roles in viral DNA transcription and replication regulation, E4, E5, E6, and E7 proteins are involved in cell cycle deregulation, immune evasion, and recruitment of replication host factors [1]. L1 and L2 late proteins constitute the major and secondary capsid proteins respectively.…”
Section: Introductionmentioning
confidence: 99%